2017
DOI: 10.3390/cryst7070226
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Halogen Bonding in Controlling Assembly and Organization of Cu(II)-Acac Based Coordination Complexes

Abstract: Abstract:In order to explore the use of non-covalent interactions in the deliberate assembly of metal-supramolecular architectures, a series of β-diketone based ligands capable of simultaneously acting as halogen-bond donors and chelating ligands were synthesized. The three ligands, L1, L2, and L3, carry ethynyl-activated chlorine, bromine, and iodine atoms, respectively and copper(II) complexes of all three ligands were crystallized from different solvents, acetonitrile, ethyl acetate, and nitromethane in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…16a). 117 Mosquera and coworkers observed that imidobridged Ti(IV) complexes with peripherally located iodine atoms can connect to tetrakis(tetrahydrofuran)-dichloromagnesium by C-I⋯Cl-Mg halogen bonding, thus demonstrating the feasibility of 2h (Fig. 16b).…”
Section: Crystengcomm Highlightmentioning
confidence: 99%
“…16a). 117 Mosquera and coworkers observed that imidobridged Ti(IV) complexes with peripherally located iodine atoms can connect to tetrakis(tetrahydrofuran)-dichloromagnesium by C-I⋯Cl-Mg halogen bonding, thus demonstrating the feasibility of 2h (Fig. 16b).…”
Section: Crystengcomm Highlightmentioning
confidence: 99%
“…[9][10][11][12][13] In contrast, the use of halogen bonding in coordination complexes, which are among the most diverse structures found in chemistry, remains comparatively unexplored. 14 In the studies that have been reported, three general strategies have emerged: firstly the design of ligands with an acceptor and donor in the same ligand (type i), [15][16][17] secondly cocrystals with either a neutral or cationic complex and halogen bonding donors (type ii) [18][19][20][21][22][23][24] and lastly complexes with two different ligands with one acting as the acceptor and the other the donor (type iii). The latter class typically uses halopyridine ligands and chelates such as -diketonates to balance the charge of the metal and satisfy the need for octahedral geometry.…”
Section: Introductionmentioning
confidence: 99%
“…As introducing metal atoms into a supramolecular material can significantly expand the possibilities of adding and controlling additional properties (such as magnetism and conductivity) [28,29], the use of halogen bonding in the crystal engineering of metal-organic materials has been an attractive challenge over the past decade [30][31][32][33][34][35][36][37][38][39][40]. While there have been substantial studies into halogen bonding in single component metal-organic solids [30][31][32][33][34][35][36][37][38][39][40][41], synthesis of multi-component materials based on halogen-bonded metal-organic components has been receiving much less attention. Particularly scarce are studies involving cocrystals of neutral metal-organic components acting as halogen bond acceptors [42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%